Identidades gaúchas : serranos, pampeanos, missioneiros e outras variações em O Tempo e o Vento - Fontana, André (My University, 2015)
The present paper approaches the “gaúchas” identities represented by characters in O Tempo e o Vento in the perspective of their variations, emphasizing the diversity inherent to the constitution of the South-Brazilian human kind. It also highligths the plurality of the rio-grandense social formation, bordering upon land and characterized by the mixture of different cultures. This trait is remarkable in Erico’s historical novel. It is in the esthetic proposal of the narrative: in the constituition, architecture and development of the Terra-Camabrá clan. Through the figure of the mountain region “gaucho”, it is possible to think of which ways several ethnic groups have interacted along time, in the process of occupation, conquer and delimitation of space. Through the counter position of the differences, the several regional identities will be able to “shine with greater splendor”, revealing some local peculiarities; distinctive signs, identity attributes that may delimit and co fuse different southern territor ies.
O trabalho aborda as identidades gaúchas representadas por personagens de O Tempo e o Vento na perspectiva de suas variações, focando a diversidade inerente a constituição do tipo humano sul-brasileiro e a pluralidade da formação social rio-grandense, terra fronteiriça e marcada pela mistura de diferentes culturas. Esse traço é marcante no romance histórico de Erico. Está na proposta estética da narrativa: na constituição, arquitetura e desenvolvimento do clã Terra-Cambará. Através da figura do gaúcho serrano busca-se pensar de que maneira as várias etnias interagiram ao longo do tempo, no processo de ocupação, conquista e delimitação do espaço. Pela contraposição das diferenças, as identidades regionais poderão “resplandecer com maior fulgor”, revelando algumas peculiaridades locais; sinais distintivos, atributos identitários que podem delimitar e cofundir diferentes territórios sulinos.
Keywords: Veríssimo, Érico, 1905-1975; O tempo e o vento (Obra literária); Literatura sul-rio-grandense - Crítica e interpretação; Literatura - História e crítica; Time and wind (Literary work); South Rio Grande literature - Criticism and interpretation; Literature - History and criticism